Ultrasound Diagnostic Accuracy in Evaluation of Obstructive Jaundice in Adults Taking MRCP as Gold Standard - Saeed, Hafiz Farzaan; Malik, Bushra; Butt, Osama; Gul, Nadia (Biological and Clinical Sciences Research Journal, 2025)
MRCP is highly sensitive in diagnosing obstructive jaundice, strictures, and malignancies, particularly in suspected cases. Although its higher accuracy in identifying the cause of obstruction makes it a sheer requirement in accurate diagnosis and treatment planning, ultrasound can be a screening modality. Objective: To determine the diagnostic accuracy of biliary tract ultrasound in diagnosing obstructive jaundice and its cause, keeping magnetic resonance cholangiopancreatography (MRCP) as the gold standard. Study Design: Cross-sectional study. Place and Duration of Study: Department of Radiology, POF Hospital, Wah Cantt, from 20th February 2024 to 19th August 2024. Methodology: A total of 300 patients aged 16 to 65 years, presenting with obstructive jaundice at the Radiology Department of POF Hospital Wah Cantt, were enrolled after informed consent. Baseline data, including age, gender, weight, and illness duration, were recorded. Patients underwent biliary tract ultrasound by a consultant radiologist for a provisional diagnosis, and the researcher noted the findings. MRCP was then performed and interpreted by a consultant radiologist to confirm the diagnosis, with results documented by the researcher. Data were collected using a predesigned proforma, ensuring patient confidentiality. Statistical analysis was conducted using SPSS version 22. Results: The mean age of the patients was 52.10±10.87 years, the mean BMI was 27.28±3.53 kg/m², and the mean disease duration was 7.01±5.86 weeks. The accuracy of biliary tract ultrasound in diagnosing obstructive jaundice was compared to MRCP as the gold standard. Specificity was 77.78%, showing that it can rule out non-obstructive cases. The positive predictive value (PPV) was 92.52%, showing that there were high chances that the people classified as positive did indeed have the disease, and the negative predictive value (NPV) was 65.12%, showing that a high proportion of negative ultrasounds still had the disease afflicting them. Ultrasonography of the biliary tract was very accurate and sensitive for all the etiologies of obstructive jaundice compared to MRCP. Conclusion: Ultrasound is moderately specific, sensitive, and accurate in diagnosing obstructive jaundice and its causes.